Widening participation and a student "success" assemblage: The materialities and mobilities of university. Issue 3 (22nd November 2019) - Wainwright, Emma; Chappell, Anne; McHugh, Ellen
Abstract: This paper takes an assemblage approach to extend knowledge and understanding of widening participation (WP) in the United Kingdom. We reflect on the identification and experiences of a WP student population—how this population has been marked out, labelled, and considered through policy and intervention, alongside the materialities and mobilities that shape the lived experiences of these students. Using questionnaire findings, narrative interviews, and photo diaries, it draws on a 12‐month study at a London university to explore the factors that have enabled final‐year undergraduate students from a WP background to stay the course and complete their programme of studies. Our arguments are shaped by the geographical and educational literatures on materialities and mobilities. We bring these together to sketch out a student success assemblage comprising wide‐ranging elements that we frame around identity, support, and resources. Assemblage draws attention to the multiplicity of human/non‐human relations that shape student experience and students' capacities for success. Assemblage intersects with university precisely through a focus on experience and, as we suggest, takes on a particular inflexion for students from a WP background. This underpinning ontological basis to studying WP enables us to view the university, student experience, and success as being continually produced and reproduced, and coconstituted between the human and non‐human. Universities should attend to student assemblages to better understand the experiences of and support needed by underrepresented groups in higher education.